2015
DOI: 10.1007/s00425-015-2358-5
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of pectin methylesterification: consequences for cell wall biomechanics and development

Abstract: Recent publications have increased our knowledge of how pectin composition and the degree of homogalacturonan methylesterification impact the biochemical and biomechanical properties of plant cell walls, plant development, and plants' interactions with their abiotic and biotic environments. Experimental observations have shown that the relationships between the DM, the pattern of de-methylesterificaton, its effect on cell wall elasticity, other biomechanical parameters, and growth are not straightforward. Work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
157
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(161 citation statements)
references
References 162 publications
(237 reference statements)
3
157
0
1
Order By: Relevance
“…A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…In PGX3 OE plants, HG molecules are smaller due to excessive PGX3 expression and more pectin degradation, which, together with the observation that there is less demethylesterified HG, leads to enhanced pectin fluidity, increased rosette size, and faster stomatal opening. (Amsbury et al, 2016), but it is currently mysterious how PME6 regulates these mechanics because removing methyl groups from pectins might result in either wall stiffening or loosening, depending on the patterns of demethylesterification (Levesque-Tremblay et al, 2015;Hocq et al, 2017). Additionally, PME34 has been implicated in stomatal responses to heat stress in Arabidopsis (Huang et al, 2017), suggesting that multiple pectin methylesterases might modulate pectin cross-linking and/or degradability in guard cell walls, adding an additional layer of complexity and control.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome contains more than 170 HG-related enzymes (Sénéchal et al, 2014), although the precise roles of only a few have been characterized to date. HG methylesterification status plays important roles in various developmental processes and is controlled tightly by pectin methylesterases (PMEs), PME inhibitors (PMEIs), subtilisin-type Ser proteases (SBTs), and at least one E3 ubiquitin ligase (Levesque-Tremblay et al, 2015). Mutants with altered expression of these players have been characterized using mAbs directed against HG domains with different degrees of methylesterification.…”
Section: Monitoring Pectic Structuresmentioning
confidence: 99%